“Acting as a unit”. A praiseworthy story from Cleveland (Italian Journal of Public Health, 2009)
This is a story that comes from Cleveland. It’s a story of zealous and ingenious men, of ideas and of cooperation. A story that is the result of various personal and diverse professional experiences, from different historical moments, all converged towards a single cause: excellence in health care. It is also a story about a private institution but nevertheless it offers many public health teachings: it’s the story of Albert Kanoti and the Cleveland Clinic Foundation. The Cleveland Clinic was founded on February 5 1921 as an independent, not-for-profit academic medical center engaged in patient care, research, and education. In 1924 it added a 184-bed hospital to its outpatient facilities. It has also experienced tragic moments, when on May 15, 1929, nitrate-based x-ray films ignited in the original building, releasing poisonous fumes; 123 people died, including Dr. Phillips, one of the founders. Despite losses from the disaster and the stock market crash, the institution stayed afloat on the good will of prominent members of the community, and the large surgical practice of Dr. Crile, another of its founders. It expanded greatly after World War II, focusing on specialized medicine. The Cleveland Clinic Research Division investigated kidney disease, blood circulation, and artificial organs, including the artificial kidney. ClevelandClinic physicians, researchers and nurses pioneered enterostomal therapy, dialysis, and kidney transplant techniques, and were first to identify carpal tunnel syndrome and isolate serotonin, and all before 1960.
Keywords: Unit; story; cleveland